2011
DOI: 10.1007/s00586-011-1864-9
|View full text |Cite
|
Sign up to set email alerts
|

Adjacent segment degenerative disease: is it due to disease progression or a fusion-associated phenomenon? Comparison between segments adjacent to the fused and non-fused segments

Abstract: Introduction The purpose of this study was to determine whether fusion causes adjacent segment degeneration or whether degeneration is due to disease progression. Materials and methods Eighty-seven patients that had undergone single level anterior cervical decompression and fusions with at least 5 years of follow-up were enrolled in this retrospective study. Segments adjacent to fusion levels (above or below) were allocated to group A, and all others were allocated to group B. Radiographic evaluations of adjac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 21 publications
(24 reference statements)
2
67
1
2
Order By: Relevance
“…Firstly, regarding the fixation area, adjacent-level failures occurred in patients who received fixation of ''O-T4'' or longer distance, which suggested that the long fusion might cause adjacent-level failures due to greater mechanical stress. In a similar way, Song et al [15,16] reported that fusion may increase mechanical stress at adjacent disc levels and lead to adjacent segment disease, and that multi-level fusion accelerated the severity of adjacent-level degeneration as compared to single-level fusion in degenerative cervical disease.…”
Section: Discussionmentioning
confidence: 87%
“…Firstly, regarding the fixation area, adjacent-level failures occurred in patients who received fixation of ''O-T4'' or longer distance, which suggested that the long fusion might cause adjacent-level failures due to greater mechanical stress. In a similar way, Song et al [15,16] reported that fusion may increase mechanical stress at adjacent disc levels and lead to adjacent segment disease, and that multi-level fusion accelerated the severity of adjacent-level degeneration as compared to single-level fusion in degenerative cervical disease.…”
Section: Discussionmentioning
confidence: 87%
“…Adjacent-segment disease has been defined as the development of new radiculopathy or myelopathy of a motion segment adjacent to the site of a previous arthrodesis of the spine (either superior or inferior). 37,42,52,91,96,100 Because this is a clinical definition, it is often confused with a radiographic definition of adjacent segment degeneration in which disc degeneration is observed at adjacent motion segments to the fusion sites. However, studies have not demonstrated a clear correlation between the radiographic changes of adjacent segment degeneration and the clinical presentation of ASD.…”
Section: Cervical Deformity and Asdmentioning
confidence: 99%
“…There is overwhelming evidence for the existence of both clinical ASD and radiographic adjacent segment degeneration, but controversy remains about the origin of the ASD or degeneration. 37,47,71,91,96,100 Investigations of whether ASD is the natural course of the spine or if adjacent spinal fusion contributes directly to ASD are still being conducted in hopes of finding a solid explanation. However, biomechanical studies have shown results of possible mechanisms of ASD.…”
Section: Cervical Deformity and Asdmentioning
confidence: 99%
“…The present armamentarium that exist with the neuro spine surgeon includes minimally invasive disc volume reducing procedures, neural decompressive procedures, lumbar fusion procedures, disc arthroplasty and posterior dynamic stabilization. The motion preserving procedures claim the benefit of preventing adjacent segment disease [2].…”
Section: Discussionmentioning
confidence: 99%